Tax Morale and Institutions - Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2003)
This paper analyses the impact of direct democracy, trust in government, the court and the legal system, and federalism on tax morale. In the tax compliance literature it is novel to analyse tax morale as dependent variable and to systematically analyse the effects of formal and informal institutions in Switzerland, a country where participation rights and the degree of federalism vary across different cantons. We used two different data sets at the individual level (World Values Survey and International Social Survey Programme). The findings suggest that direct democratic rights, local autonomy, and trust in government, the court and the legal system have a significantly positive effect on tax morale.
Keywords: H26; H73; D70; 330; Tax Morale; Tax Compliance; Tax Evasion; Direct Democracy; Local Autonomy